2002
DOI: 10.1258/002367702320389080
|View full text |Cite
|
Sign up to set email alerts
|

Rats' preferences for corn versus wood-based bedding and nesting materials

Abstract: Corn by-products can be used as bedding and nesting products. Corn-cob bedding resists ammonia build-up and corn-husk nesting material resists dampness. It is not clear whether these advantages are at the expense of animal comfort. Corn cob was compared to aspen chip bedding, and corn husk to paper strip nesting material. Data from 20 rats with differential early bedding experience suggested that they prefer aspen chip, but are also biased towards the bedding they were raised on. Data from 10 rats with no prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…There is no literature regarding this possible preference for nesting materials in rabbits, whereas in other species such as hamsters (Lanteigne and Reebs, 2006), rats (Ras et al, 2002), mice (Van de Weerd et al, 1997) or laying hens (Kruschwitz et al, 2008), some works have been done.…”
Section: Discussionmentioning
confidence: 99%
“…There is no literature regarding this possible preference for nesting materials in rabbits, whereas in other species such as hamsters (Lanteigne and Reebs, 2006), rats (Ras et al, 2002), mice (Van de Weerd et al, 1997) or laying hens (Kruschwitz et al, 2008), some works have been done.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the health benefits of the paper bedding, its use might improve rat welfare, although we found no clear evidence that it increased welfare per se (as opposed to health) in this study. Also, we know of no preference studies that have used anything similar to Alpha-Dri, and in fact aspen beddings have to date been preferred by rats and mice when compared against a variety of other beddings (Mulder 1975, Odynets et al 1991, Ras et al 2002. Currently many medical and toxicity studies use wire cages to avoid interference from bedding materials, but it would be useful to discover if Alpha-Dri and similar products are as inert as wire; if so, perhaps their use could enrich the animals' environments without compromising the quality of research.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 2 showed that technicians fill cages to reach a desired depth of bedding, rather than to provide a desired mass of it (see also Gamble & Clough 1976, Ras et al 2002. Indeed, bedding depth (and therefore volume) is probably the more relevant aspect for the animals concerned, since it must be deep enough to lie on and dig in for example, but not so deep that it contacts the water spout and floods the cage, or impairs the animals' movement.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, absorbency by volume would be a more relevant measure as beddings tend to be placed in rodent cages to fill a certain volume or depth, not to reach a given mass (e.g. Gamble & Clough 1976, Ras et al 2002. Therefore, this study aimed to distinguish the absorbencies of six beddings marketed for use in rodent cages, and to compare their volumetric absorbencies with their equivalent absorbencies by mass (Experiment 1).…”
mentioning
confidence: 99%